Electrostatic potential fluctuations and light‐soaking effects in Cu(In, Ga)Se2 solar cells. (18th June 2020) - Nikolaeva, Aleksandra; Krause, Maximilian; Schäfer, Norbert; Witte, Wolfram; Hariskos, Dimitrios; Kodalle, Tim; Kaufmann, Christian A.; Barreau, Nicolas; Abou‐Ras, Daniel
Abstract: In Cu(In, Ga)Se2 (CIGS) thin‐film solar cells, laterally inhomogeneous distributions of point defects may induce electrostatic potential fluctuations and thus reduce the open‐circuit voltage ( V oc ). In the present work, we investigate possible origins of fluctuating potentials and estimate the amplitude of fluctuations and V oc losses in solar cells with various [Ga] in the CIGS absorber, with different buffer layers and with different durations of an RbF postdeposition treatment (PDT). Electron‐beam‐induced current measurements were employed to study the local difference in the width of the space‐charge region ( w SCR ). It is shown that the amplitude of fluctuations in the w SCR depends significantly on the choice of buffer system and on the duration of the RbF PDT. In addition, energy‐dispersive X‐ray spectroscopy and cathodoluminescence measurements reveal that band‐gap fluctuations do not have substantial impact on the device performance. Finally, some of the investigated cells were exposed to light soaking, which was found to be a means to reduce the detected electrostatic potential fluctuations and also to increase the effective electron diffusion length in the CIGS absorber for a part of the investigated cells. Abstract : It is shown that the dominant effect of electrostatic potential fluctuations in Cu(In, Ga)Se2 solar cells is linked to the local variations in the doping densities N D and the interface‐charge density N IF introduced via the buffer layer deposition or duration of RbF postdeposition treatment. Furthermore, light soaking was found to reduce electrostatic fluctuations in cells with Zn(O, S) buffer. To explain this, we proposed a model based on changes in charge states of defects at the CIGS/buffer interface.